Surprising cause of dysphagia in an elderly male - Kyle Bennett; Suzanne Supplee; Priyanka Vyas; Shuchi Gulati; Richard Alweis (Greater Baltimore Medical Center, 2014)
A 73 year old man presented to his primary care physician with sudden onset dysphagia to solids and liquids. He urgently completed a barium swallow study showing what was believed to be a coin. Endoscopic removal subsequently revealed it was a lithium battery. Consequences and management of lithium battery ingestion are discussed.